OPRM1 rs1799971 polymorphism and opioid dependence: evidence from a meta-analysis. (May 2013) - Haerian, Batoul Sadat; Haerian, Monir Sadat
The OPRM1 gene encodes the µ-opioid receptor, which is the primary site of action of most opioids. Several studies and three meta-analyses have examined a possible link between the exonic OPRM1 A118G (rs1799971) polymorphism and opioid dependence; however, results have been inconclusive. Therefore, a systematic review and meta-analysis have been carried out to examine whether this polymorphism is associated with opioid dependence. Thirteen studies (n = 9385), comprising 4601 opioid dependents and 4784 controls, which evaluated association of the OPRM1 rs1799971 polymorphism with susceptibility to opioids, were included in this study. Our meta-analysis showed significant association between this polymorphism and susceptibility to opioid dependence in overall studies under a codominant model, as well as susceptibility to opioid dependence or heroin dependence in Asians under an autosomal dominant model. The nonsynonymous OPRM1 rs1799971 might be a risk factor for addiction to opioids or heroin in an Asian population.